New Perspectives on Burnout: A Controlled Study on Movement Analysis of Burnout Patients - Pfeffer, Manuela M.; Paletta, Andrea; Suchar, Gerald (Frontiers in Psychology, 2018)
Introduction: Despite extensive research on burnout, there has been to date no systematic movement analysis of burnout patients, although it is well known that psychiatric diseases express themselves through movements, such as psychomotor retardation or agitation. Since the movement expression of burnout patients has not been systematically investigated so far, the aim of this study is to close this knowledge gap in order to obtain a new perspective on burnout. Methods: Hospitalized burnout patients (n = 22; age 47.2 ± 9.1 years) and health controls (n = 20; age 41.5 ± 15.0 years) participated in a standardized movement sequence with verbal instructions. The objective Burnout Inventory Scale and diagnostics by psychiatrists were used for diagnosis. Two certified movement-analysts independently rated each participant via video by using the Effort System of Laban Movement Analysis as an instrument of dance therapy and behavior observation. Cohen’s Kappa was used to test the inter-rater reliability of the movement analysts and non-parametric Mann-Whitney U tests were undertaken to assess the differences between the two groups. Results: The rater-agreement Kappa ranges from .66 to .92 (p < .001) with the Confidence Interval (95%) from .46 to 1.1. Results of the Mann-Whitney U tests indicate that burnout patients show significantly less frequent movements for the following Effort elements: Bound U(n1 = 22, n2 = 20) = 112.5, p = .001; Indirect U(n1 = 22, n2 = 20) = 114.5, p = .001; Light U(n1 = 22, n2 = 20) = 115, p = .001 and Sustained U(n1 = 22, n2 = 20) = 130, p = .01. Discussion: Burnout patients have significant deficits in all four Effort elements of the Laban Movement Analysis (Flow, Space, Time, Weight) and therefore have deficits regarding their body movement. The findings presented here provide an additional perspective on burnout.